"It's From a Fresh Perspective": Children's Reflections on Participation in Ecological Research and Action - Jagger, Susan (The Canadian Journal of Action Research)

(untitled) (Canadian Association of Action Research in Education, 2025)
Environmental education looks to motivate and empower positive environmental actions that respect the complexity of natural systems. It follows that related educational research takes up a multiplicity of voices, and possibilities for exploring ecological curriculum and practice. Participatory action research (PAR) does this as it brings together theory, inquiry, and social justice, and PAR that includes children as researchers is transformative for both young researchers and the community. There is, however, limited research on the experiences of young learners in PAR in environmental education. This paper shares the reflections of the Eco Research Organization, a group of grade six researchers, and Susan Jagger, their adult co-researcher, on their engagement in PAR in a longitudinal study of their school garden and nature in their community.